Keeping a low profile: What determines the allocation of aid by non-governmental organizations? - Dirk-Jan Koch; Axel Dreher; Peter Nunnenkamp; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2008)
NGOs play an important role in international development cooperation, but the allocation of NGO aid has rarely been mapped, let alone explained. Based on a representative dataset for 61 important NGOs from various OECD countries, we analyze the targeting of NGO aid across a large number of recipient countries by jointly considering major determinants of NGO aid in a multivariate regression framework. While our results show that NGOs are more active in the neediest countries, we reject the hypothesis that NGOs complement official aid through engaging in so-called difficult institutional environments. Rather, they tend to replicate the location choices of official ?backdonors.? Moreover, NGOs follow other NGOs so that aid gets clustered. Finally, NGOs select recipient countries with common traits related to religion or colonial history. Taken together, our findings suggest that NGOs keep a low profile rather than distinguishing themselves from other donors and trying to excel under risky conditions.
Keywords: F35; 330; Aid agencies; Non-governmental organizations; Poverty; Aid allocation; Entwicklungskooperation; Nichtregierungsorganisation; OECD-Staaten; Armut; Entwicklungshilfe; Entwicklungsländer; Schätzung